2014
DOI: 10.1021/es504053f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygenated Fuels on Physicochemical and Toxicological Characteristics of Diesel Particulate Emissions

Abstract: A systematic study was conducted to make a comparative evaluation of the effects of blending five different oxygenates (diglyme (DGM), palm oil methyl ester (PME), dimethyl carbonate (DMC), diethyl adipate (DEA), and butanol (Bu)) with ultralow sulfur diesel (ULSD) at 2% and 4% oxygen levels on physicochemical and toxicological characteristics of particulate emissions from a nonroad diesel engine. All blended fuels led to an overall decrease in the particulate mass concentration and elemental carbon (EC) emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 34 publications
1
18
2
Order By: Relevance
“…The use of DMC resulted in statistically significant increases in particle number emissions compared to CARB ULSD, ranging from 66% to 141%. Our results are in contrast with those seen in previous studies of DMC where particle number emissions showed reductions with higher concentrations of DMC in diesel fuel [21,25,33]. Zhang and Balasubramanian [25] found reductions in particle number emissions of 25.1% and 36.1% for 5% and 10% DMC blends, respectively, based on measurements with a fast mobility particle sizer (FMPS), while Cheung et al [21] also showed reductions in particle number on average of 21% and 37%, for 9.1-18.6% DMC blends, respectively.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…The use of DMC resulted in statistically significant increases in particle number emissions compared to CARB ULSD, ranging from 66% to 141%. Our results are in contrast with those seen in previous studies of DMC where particle number emissions showed reductions with higher concentrations of DMC in diesel fuel [21,25,33]. Zhang and Balasubramanian [25] found reductions in particle number emissions of 25.1% and 36.1% for 5% and 10% DMC blends, respectively, based on measurements with a fast mobility particle sizer (FMPS), while Cheung et al [21] also showed reductions in particle number on average of 21% and 37%, for 9.1-18.6% DMC blends, respectively.…”
Section: Resultscontrasting
confidence: 99%
“…Overall, PM mass emissions showed substantial reductions with DMC application compared to CARB ULSD ranging from 30% to 78%, with these reductions being statistically significant. The results reported here are in good agreement with previous studies showing strong reductions in PM and soot emissions with DMC-diesel blends [16,17,25,26], as well as studies of other oxygenates such as biodiesel [27][28][29][30]. In comparison with biodiesel, however, the percentage reductions for the DMC are much larger than those seen for biodiesel for a comparable blend level.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations